ENHANCEMENT THE OPTICAL PROPERTIES OF ZINC SULFIDE THIN FILMS FOR SOLAR CELL APPLICATIONS - Saeed, Nada; Suhail, A. (Iraqi Journal of Science, 2024)
In this work, semi-conducting ZnS compound was prepared as thin films onto glasssubstrates at two different substrates temperature (673, 723) K using chemical spraypyrolysis technique. X-ray diffraction was studied for the prepared films, the resultsshows that the films was polycrystalline with a wurtzite (hexagonal) structure. Theoptical properties of the films were studied by using VIS-UV spectrophotometer, theabsorbance and transmittance spectrum have been recorded at wavelength within therange (300-900) nm. The optical characteristics were studied as a function of thephoton energy at the mentioned wavelength. The results appear that the transparencyof the films at visible region is rise from 70% to 90% at high substrates temperature.The refractive index was estimated within the visible wavelength at 500 nm, it was2.45 at substrate temperature 673 K and its value will decrease at the highestsubstrate temperature. The direct optical band gap of the allow transitions for thedeposits films prepared at both substrate temperatures (673, 723) K were variedfrom 3.2-3.4 eV respectively.